Contribution of virtual reality (nintendo wii) for exercise training and rehabilitation - Hiraga, Cynthia Yukiko [UNESP]; Tonello, Maria Georgina Marques; Pellegrini, Ana Maria [UNESP] (Springer Nature, 2017)
The purpose of this chapter is to discuss the use of a commercially available video game console for intervention and/or rehabilitation. This chapter is organized into four main topics. The first one focuses on technology and basic principles and concepts of Nintendo Wii. The technology behind of the Wii gaming system will be described emphasizing the aspects regarding the relevance of such technology to motor behavior. The second topic describes the effect of Wii gaming system in older adults without movement disorders, on healthy aging. Exercise training based on the use of Wii gaming may have a positive impact on metabolic parameters and functional capacity such as balance as a result of aging process. The third topic describes the effect of Wii gaming for rehabilitation of stroke patients. The use of Wii gaming for stroke patients may bring some positive outcomes for motor recovery. Finally, the fourth topic discusses some of the relevant underlying mechanisms of motor learning related with the use of Wii gaming system for health exercising and rehabilitation.
Keywords: Ageing; Balance; Health; Intervention; Motor learning; Nintendo wii; Practice; Rehabilitation; Stroke patients; Virtual reality